THE ANALYSIS OF MOTION DETECTION METHODS IN DIGITAL VIDEO SURVEILLANCE SYSTEMS - Mikhail Grigorievich Babenko; Viktor Andreevich Kuchukov; Ekaterina Andreevna Kuchukova; Natalia Grigorievna Gudieva (Современная наука и инновации, 2022)
The article examines various methods of motion detection in the video stream. The modeling on the microcomputer Raspberry Pi 2 was carried out. The possibility of applying the residue number system for this problem was investigated, the scheme of the motion detection device operating in the residue number system is given.